On the dynamics of a chemostat model with delayed nutrient recycling - Fergola, Paolo; Jiang, Liqiang; Ma, Zhien (Zielona Góra: Uniwersytet Zielonogórski)
This paper studies the dynamics of a chemostat model with n populations competing for one nutrient which can be recycled due to decomposition of dead biomass. Several kinds of results about local and global stability of non-negative equilibria, uniform persistence and control of populations are obtained.
Keywords: chemostat model; delayed nutrient recycling; stability; uniform persistence; population control